PENINGKATAN PEMBELAJARAN GERAK DASAR ATLETIK DENGAN PERMAINAN POS BERANGKAI (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The  purpose  of  this  study was  to  determine  the  presence  or  absence  of  an  increase  in  learning  basic  athletic motion with sequential post game at third grade students of SDN 01 Sidosari Kesesi Pekalongan 2014 This study is a Class Action Research (Classrom Action Research), the results of  studies using 2 cycles. Each cycle begins with planning, action, observation / evaluation and reflection. As many as 24 students study subjects consisted  of  16  boys  and  8  female  student.  Data  collection  is  done  by  using  the  data  field  observations  and questionnaires obtained from the evaluation. In a study shows in the first cycle with the value of the percentage of completeness 58% value is less satisfactory. Then resumed on the second cycle with a percentage value 92% value  produced  in  accordance  with  desired.  From  the  research  that has  been  done  can  be  seen  that  the  post game  sequential  increase  capacity  and  student  learning  outcomes  in  basic  athletic  motion  at  third  grade students  of  SDN  01  Sidosari.  Improved  athletic  student  learning  basic  movement  using  the  postal  game sequential mastery shown by the percentage value of greater that 92%.